Exploration of correlation of oral hygiene and condition with influenza infection. - Makiko Kawamoto (Public Library of Science (PLoS), 2021)
Influenza viruses are known to be infected through epithelial cells of the upper respiratory tract. The oral cavity is in close anatomical proximity to the upper respiratory tract, and it is conceivable that the viruses could pass through the oral cavity and infect to the upper respiratory tract. Several researchers have suggested that colonization of certain pathogenic bacteria such as Staphylococcus aureus or Streptococcus pneumoniae might affect the risk of influenza viral disease, indicating that oral hygiene and/or condition might play an important role in respiratory viral infection. Therefore, the purpose of this study was to investigate whether an oral hygiene/condition might impact influenza infection. We conducted a retrospective observational study of Japanese citizens' regional cohort (N = 2,904) consisting of National Health Insurance beneficiaries who underwent annual health/dental examination with data entries in the Kokuho database (KDB). Trained dentists checked the oral hygiene/condition, and saliva specimens were examined using the LION dental saliva multi-test (SMT) kit. Influenza infection was identified from the diagnosis recorded in the KDB. The correlations between influenza infection and oral hygiene, dryness of the mouth, or various salivary test results were examined by a multivariate analysis adjusting for confounding factors such as gender, age, recent smoking, alcohol drinking, BMI, HbA1c, RBC for influenza infection. The logistic regression model showed that age significantly correlated with influenza infection. In addition, oral hygiene status had a nearly significant impact on influenza infection (p = 0.061), whereby, the subjects with poor oral hygiene had a higher risk of influenza infection than those with good oral hygiene (odds ratio: 1.63, 95% confidence interval: 0.89-2.95). Further, the prevalence of influenza infection was lower in the subjects with saliva weakly acidic and/or containing higher protein level. The results of this study suggested that the maintenance of oral health conditions might be one of the pivotal factors for preventing and reducing influenza infection.